2018
DOI: 10.1093/ofid/ofy210.1658
|View full text |Cite
|
Sign up to set email alerts
|

2002. Evaluation of the BioFire® Pneumonia Panel in ICU Patients With Suspected Ventilator-Associated Pneumonia

Abstract: BackgroundVentilator-associated pneumonia (VAP) is one of the most commonly encountered hospital-acquired infections worldwide, and one of the major contributors to an over mortality in critically ill patients. Initial empirical antimicrobial therapy is often broad-spectrum. Fast identification and quantification of microorganisms is of great importance to enable early effective targeted antimicrobial treatment. This trial compares the performance of the new BioFire® Pneumonia Panel (BPP) with quantitative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The overall percent agreement between the Fil-mArray panels and conventional bacterial culture in our study was 100%, with 100% PPA and 29.9% NPA. This was concordant with Iannello et al who reported 89.0% PPA and 95.9% NPA with bacterial culture [24]. Edin and his team demonstrated 100% PPA and 73.2% NPA [25].…”
Section: Pathogens Detected Using Biofire Filmarraysupporting
confidence: 89%
“…The overall percent agreement between the Fil-mArray panels and conventional bacterial culture in our study was 100%, with 100% PPA and 29.9% NPA. This was concordant with Iannello et al who reported 89.0% PPA and 95.9% NPA with bacterial culture [24]. Edin and his team demonstrated 100% PPA and 73.2% NPA [25].…”
Section: Pathogens Detected Using Biofire Filmarraysupporting
confidence: 89%
“…The PN panel expands on these existing technologies to provide an easy-to-use, rapid sample-to-answer platform that can detect viral entities and atypical bacteria known to cause pneumonia, in addition to providing a semiquantitative result for 15 commonly encountered bacterial analytes. An earlier study using an RUO version of the PN panel on BAL from patients suspected of having ventilator-associated pneumonia concluded that the panel would provide data that could guide appropriate management in this patient population (36).…”
Section: Resultsmentioning
confidence: 99%
“…Edin demonstrated for on-panel pathogens a PPA of 100% and an NPA of 73.2% [ 25 ], and Gastli demonstrated a PPA of 94.4% and an NPA of 96.0% as compared to culture [ 26 ]. Similarly, a VAP study using a research use only version of BioFire PN plus Panel demonstrated for bacteria an 89.0% PPA and 95.9% NPA with SOC [ 27 ]. BioFire PN plus Panel reflects high performance compared to SOC, yielding additional clinically actionable results that may be missed by SOC.…”
Section: Discussionmentioning
confidence: 99%